2010
DOI: 10.4317/jced.2.e67
|View full text |Cite
|
Sign up to set email alerts
|

Frozen section evaluation of lymph nodes in Oral squamous cell carcinoma - A retrospective study

Abstract: The principal indication of performing a frozen section is to obtain a definite immediate diagnosis, on the basis of which a surgical decision will be made. Immediate diagnosis allows the surgeon to proceed with further therapy without any delay. A definite immediate diagnosis is said to be dependent on the reliability of frozen sections. Many authors have carried out frozen section study on soft tissue tumors and lymph node evaluation in different parts of the body with varying percentages of reliability. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Adipose tissue should therefore be removed as far as possible and several sections should be prepared to allow accurate observation of all sections of the lymph nodes. 9 In this study the sensitivity of frozen section is around 32.5% with a specificity of 97.1%. This is in accordance with the study by Rassekh CH et al on cervical lymph nodes for metastasis from aero digestive tract neoplasm and in which accuracy of 92.3% was determined.…”
Section: Roc Curvementioning
confidence: 52%
See 1 more Smart Citation
“…Adipose tissue should therefore be removed as far as possible and several sections should be prepared to allow accurate observation of all sections of the lymph nodes. 9 In this study the sensitivity of frozen section is around 32.5% with a specificity of 97.1%. This is in accordance with the study by Rassekh CH et al on cervical lymph nodes for metastasis from aero digestive tract neoplasm and in which accuracy of 92.3% was determined.…”
Section: Roc Curvementioning
confidence: 52%
“…10 Wada et al &Kurosumi et al who have reported intraoperative sensitivity for lymph nodes in breast cancer in the range of 47% to 74% whereas in melanoma the sensitivity ranges from 38% to 47% [Ferris]. 9,4 Many patients have to undergo second surgeries to complete lymph node dissection in cases in which definitive pathologic assessment identifies metastasis that were missed on the frozen section examination. The limitation of frozen section is that it is most accurate at detecting the foci of nodal metastasis that are > 2mm in size, therefore deposits less than 2mm are missed.…”
Section: Roc Curvementioning
confidence: 99%
“…A definite immediate diagnosis is said to be dependent on the reliability of frozen sections. 15 Many authors have carried out frozen section study on soft tissue tumors and margins evaluation in the different parts of body, with varying percentages of reliability. 12,16 Frozen sections have been used both in the diagnosis and to evaluate margins.…”
Section: Discussionmentioning
confidence: 99%
“…In most publications, accuracy for such diagnosis is 96.8% to 98%. 7,13,15,17 The diagnosis on lesions in different regions of the body were varied in their accuracy form 91.5% to 98%, 10 and in head and neck neoplasm 96% to 99%. 3,7,17 There are essentially two main sources of frozen section errors.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative evaluation of lymph nodal metastasis in head and neck carcinoma assumes importance in deciding the extent of lymph node dissection. Accuracy of the FZ has been studied extensively in the evaluation of margin status in head and neck cancer, whereas studies analyzing the use of FZ in the evaluation of neck nodes in head and neck cancer are limited 5,7‐15 . In most of these studies, the specificity of the FZ in the evaluation of neck nodes in head and neck cancer is close to 100% whereas sensitivity varies from 43% to 93%.…”
Section: Discussionmentioning
confidence: 99%